Human papillomavirus infection and biomarkers in sinonasal inverted papillomas: clinical significance and molecular mechanisms. Issue 8 (16th June 2015) - Scheel, Adam; Lin, Giant C.; McHugh, Jonathan B.; Komarck, Christine M.; Walline, Heather M.; Prince, Mark E.; Zacharek, Mark A.; Carey, Thomas E.
<x xml:space="preserve">Abstract</x> Background The role of human papillomavirus (HPV) in sinonasal inverted papillomas (IPs) is controversial. Determining the prevalence of HPV infection and its impact on the molecular biology of these tumors is critical to characterizing its role in the pathogenesis of IPs. Methods A total of 112 paraffin‐embedded IPs from 90 patients were studied. A tissue microarray was constructed and stained for p16, p53, epidermal growth factor receptor (EGFR), and cyclin D1. HPV presence and types were determined using PGMY 09/11 primers and integration using HPV 11 detection of integrated papillomavirus sequences by ligation‐mediated polymerase chain reaction (DIPS‐PCR). Results HPV was detected in 11 of 90 (12%) patients. HPV 11 was found in 9 samples. HPV 6 and HPV 27 were found in 1 sample each. EGFR staining proportion was higher in HPV‐positive IPs vs HPV‐negative specimens (56.2% vs 23.6%; p = 0.009). Differences in p16, p53, and cyclin D1 staining were not significant. HPV‐positive lesions tend to progress to malignancy (p = 0.064). Three samples were analyzed for integration. Viral integration was found in both malignant tumors but not in the precursor IP. Conclusion Degradation of p53 and p16/cyclin D1 dysregulation are not important mechanisms in low‐risk HPV‐related IP. The low prevalence of HPV in this series indicates it is not a main etiological factor for IPs; however, when present, low‐risk HPV may contribute to the biology of IPs through an increase of EGFR expression and a predisposition for malignant progression by integration into the cellular genome.